The calcaneum as a site for intraosseous infusion. Issue 6 (November 1998) - McCarthy, G; Buss, P
Abstract : Intraosseous infusion has been recommended as a rapid and effective form of circulatory access in the collapsed child. Recognised sites for insertion include the tibia, femur, iliac crest, sternum, and clavicle. The case of a 3 year old collapsed child is described who was successfully resuscitated with the use of an intraosseous needle placed in the calcaneum; the method of needle insertion is also detailed.